Vitamin D deficiency and supplementation in patients with aggressive B‐cell lymphomas treated with immunochemotherapy - Hohaus, Stefan (Cancer Med, 2017)
Vitamin D deficiency has been reported to be a negative prognostic factor in elderly patients with aggressive B‐cell lymphomas. In vitro data suggest that vitamin D supplementation may enhance rituximab‐mediated cytotoxicity. We prospectively assessed 25‐hydroxyvitamin D [25(OH)D] levels at diagnosis in a cohort of 155 patients with aggressive B‐cell lymphomas of whom 128 had diffuse large B‐cell lymphoma (DLBCL) not otherwise specified. 25(OH)D levels were deficient (<20 ng/mL) in 105 (67%), insufficient (20–29 ng/mL) in 32 (21%), and normal (≥30 ng/mL) in 18 (12%) patients with a seasonal variation. Patient characteristics associated with lower 25(OH)D levels were poor performance status, overweight, B‐symptoms, elevated LDH, lower albumin and hemoglobin levels. As a result of a change in practice pattern, 116 patients received vitamin D3 (cholecalciferol) supplementation that included a loading phase with daily replacement and subsequent maintenance phase with a weekly dose of 25,000 IU until end of treatment. This resulted in a significant increase in 25(OH)D levels, with normalization in 56% of patients. We analyzed the impact of 25(OH)D levels on event‐free survival in patients treated with Rituximab‐CHOP. 25(OH)D levels below 20 ng/mL at diagnosis and IPI were independently associated with inferior EFS. Moreover, patients with normalized 25(OH)D levels following supplementation showed better EFS than patients with persistently deficient/insufficient 25(OH)D levels. Our study provides the first evidence that achievement of normal 25(OH)D levels after vitamin D3 supplementation is associated with improved outcome in patients with DLBCL and deficient/insufficient 25(OH)D levels when receiving rituximab‐based treatment.